2013
DOI: 10.1371/journal.pone.0080784
|View full text |Cite
|
Sign up to set email alerts
|

Triptolide Induces Growth Inhibition and Apoptosis of Human Laryngocarcinoma Cells by Enhancing p53 Activities and Suppressing E6-Mediated p53 Degradation

Abstract: Triptolide, an active compound extracted from Chinese herb Leigongteng (Tripterygium wilfordii Hook F.), shows a broad-spectrum of anticancer activity through its cytotoxicity. However, the efficacy of triptolide on laryngocarcinoma rarely been evaluated, and the mechanism by which triptolide-induced cellular apoptosis is still not well understood. In this study, we found that triptolide significantly inhibited the laryngocarcinoma HEp-2 cells proliferation, migration and survivability. Triptolide induces HEp-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
24
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(28 citation statements)
references
References 52 publications
4
24
0
Order By: Relevance
“…Triptolide (PG‐490), which is a diterpenoid triepoxide purified from a Chinese herb Tripterygium wilfordii Hook F, is the major component responsible for the immunosuppressive and anti‐inflammatory effects of T. wilfordii . Besides, triptolide has the effects of inhibiting proliferation and inducing apoptosis . We confirmed that triptolide inhibited airway remodelling in ovalbumin‐sensitized mice in our previous work .…”
Section: Introductionsupporting
confidence: 88%
See 1 more Smart Citation
“…Triptolide (PG‐490), which is a diterpenoid triepoxide purified from a Chinese herb Tripterygium wilfordii Hook F, is the major component responsible for the immunosuppressive and anti‐inflammatory effects of T. wilfordii . Besides, triptolide has the effects of inhibiting proliferation and inducing apoptosis . We confirmed that triptolide inhibited airway remodelling in ovalbumin‐sensitized mice in our previous work .…”
Section: Introductionsupporting
confidence: 88%
“…Besides, triptolide has the effects of inhibiting proliferation and inducing apoptosis. 7,8 We confirmed that triptolide inhibited airway remodelling in ovalbumin-sensitized mice in our previous work. 9 However, the mechanism of how triptolide affects airway remodelling remains unclear.…”
Section: Introductionsupporting
confidence: 86%
“…Besides, triptolide has the effects of inhibiting proliferation and inducing apoptosis [5][6][7]. We have confirmed that triptolide inhibited airway remodeling in OVA-sensitized mice [8].…”
Section: Introductionsupporting
confidence: 67%
“…Furthermore, the anti-cancer effect of TPL is attributed to its cytotoxicity. We found that TPL is cytotoxic to both cancer cells and normal cells in vitro , although the cytotoxic effect of TPL on normal cells is less than on cancer cells 53. The toxicity of TPL is dose-dependent.…”
Section: Discussionmentioning
confidence: 78%